Inventarisasi Semut yang Ditemukan pada Perkebunan Buah Naga Lubuk Minturun, Kota Padang dan Ketaping, Kabupaten Padang Pariaman, Sumatera Barat - Ranny Ranny; Henny Herwina; Dahelmi Dahelmi (Jurnal Biologi Universitas Andalas, 2015)
An inventory of ants from dragon fruit plantation at Lubuk Minturun and Ketaping, West Sumatra was made from July to September 2013 by using modified Quadra Protocol methods including honey bait trap, soil core sampling and direct collection. Twelve species of ants that belong to four subfamilies, 10 genera and 2807 individuals were collected from both locations. The highest number of species was found in Myrmicinae (four species), followed by Dolichoderinae (three species), Formicinae (three species) and the lowest number of species was found in Ponerinae (one species). Each species was described based on morphological characteristics.Keywords: ant, inventory, dragon fruit plantation, quadra protocol method